Use of Biologic Medicine in Autoimmune and Inflammatory Diseases; Effectiveness, Side-Effects and Loss of Strength in the Long Run, Then What? - Magbri, Awad; El-Magbri, Mariam (British Journal of Healthcare and Medical Research, 2024)
The use of biological medicines has revolutionized the treatment of various chronic and immune-mediated diseases, offering improved outcomes in gastrointestinal disorders like ulcerative colitis (UC) and Crohn’s disease (CD), rheumatological diseases such as systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA), and skin conditions like psoriatic arthritis (PsA) and eczema, among others. These therapies, often in the form of monoclonal antibodies or cytokine inhibitors, target specific immune pathways, providing relief where traditional treatments often fall short. While these drugs have transformed the management of these conditions, their long-term efficacy and safety present significant challenges, particularly with the emergence of subtle side effects, such as the development of new autoimmune diseases and neutralizing antibodies that render these drugs less effective over time.